Case study of radial fibrolamellar bone tissues in the outer cortex of basal sauropods. (2nd March 2020) - Jentgen-Ceschino, Benjamin; Stein, Koen; Fischer, Valentin
Abstract : The histology of sauropod long bones often appears uniform and conservative along their evolutionary tree. One of the main aspects of their bone histology is to exhibit a fibrolamellar complex in the cortex of their long bones. Here, we report another bone tissue, the radial fibrolamellar bone (RFB), in the outer cortex of the humeri of a young adult cf. Isanosaurus (Early to Late Jurassic, Thailand) and an adult Spinophorosaurus nigerensis (Early to Middle Jurassic, Niger) that do not exhibit any pathological feature on the bone surface. Its location within the cortex is unexpected, because RFB is a rapidly deposited bone tissue that would rather be expected early in the ontogeny. A palaeopathological survey was conducted for these sampled specimens. Observed RFB occurrences are regarded as spiculated periosteal reactive bone, which is an aggressive form of periosteal reaction. A 'hair-on-end' pattern of neoplasmic origin (resembling a Ewing's sarcoma) is favoured for cf. Isanosaurus, while a sunburst pattern of viral or neoplasmic origin (resembling an avian osteopetrosis or haemangioma) is favoured for Spinophorosaurus . This study highlights the importance of bone histology in assessing the frequency and nature of palaeopathologies. This article is part of the theme issue 'Vertebrate palaeophysiology'.